Efficacy of RUTI® immunotherapy against active tuberculosis in a mouse model challenges the Koch phenomenon - Soldevilla, Pablo; Buisan, Anna; Diaz, Jorge; Saladrigas, Sergi; Rosales, Yaiza; Arias, Lilibeth; Jimenez-Melsio, Alexandra; Vilaplana, Cristina; Amat Fabregat, Merce; Cardona, Pere-Joan (Frontiers in Tuberculosis, 2023)
Objectives The objective of this study was to evaluate the safety and efficacy of the therapeutic vaccine RUTI® with or without the standard of care (SOC) chemotherapy for TB in an experimental murine model. Methods We assessed the efficacy of RUTI®, a vaccine based on pasteurized and freeze-dried cell-wall fragments from Mycobacterium tuberculosis (Mtb), the SOC for sensitive TB (isoniazid, rifampicin, ethambutol, and pyrazinamide) in the murine active TB model in C3HeB/FeJ strain (Kramnik model). We evaluated the bacillary load in the lungs and spleen, the immune response against specific Mtb antigens (PPD, HSP16.3, ESAT-6, and PsTS1), and lung damage in paraffined tissues for qualitative and quantitative analysis. Results RUTI® significantly reduces the pulmonary damage (x3) and the bacterial burden in the lungs (1.5 log10) and spleen (1 log10), and maintains the cellular immune response against ESAT-6, compared to SOC. There was also an additive effect when administered in combination with SOC, increasing the reduction of the lung damage (x2), the bacillary load in lungs (1 log10) and increasing the immune response against PPD, HSP16.3 and PsTS1. Discussion Therapeutic vaccination against TB has been avoided for decades due to fear of toxicity through the Koch phenomenon. These data show for the first time the safety of immunotherapy with Mtb antigens in an active TB model, adding efficacy to SOC. This encourages the beginning of clinical studies to evaluate the safety and efficacy of RUTI® in TB patients to improve their health, reduce its potential infectiousness, and reduce the length of treatment.